N-acetykysteine reduces myocardial injury progression in experimental models - Perez, Alicia Garcia; Viera, Leydi Mora; Abreu Reyes, David R. [UNESP] (Cardiocentro Ernesto Che Guevara, 2020)
N-acetylcysteine is known in a number of medical specialties and its ability to decrease the impact of reperfusion injury in acute myocardial infarction has boosted its use in cardiology over the past decades. N-acetylcysteine has a far-reaching range of effects since it functions as a protective agent against oxygen radicals through sulfhydryl groups in important regions of the cell membrane that interfere and affect endothelial functioning and complex adhesion processes as side effects; as well as other phenomena of the extravascular compartment. These processes are closely related to the cardiovascular system.
Keywords: Myocardial injury; Reperfusion injury; Oxidative stress; N-acetylcysteine